Toward efficient mitigation solutions: Source‐based carbon pricing and economic implications in China - Xiaokun Wang; Lin Zhu; Hua Liao (Journal of Industrial Ecology, 2025)
The introduction of carbon pricing policies has emerged as a critical global strategy to mitigate climate change and reduce greenhouse gas emissions. However, the effectiveness of these policies depends on the accuracy of carbon emissions data and their alignment with the social costs of emissions. Traditional carbon pricing mechanisms, often focused on downstream emitters, face challenges such as data inaccuracies, limited coverage, and implementation complexities. This paper explores an alternative approach: source‐based carbon pricing, which targets emissions at their origin—primarily from fossil fuel combustion and industrial processes. By imposing charges at the source, this method enhances emissions coverage and simplifies implementation compared to conventional emitter‐focused models. Using a social accounting matrix) model, this study conducts a detailed economic analysis of carbon pricing's effects across various sectors. The findings highlight significant impacts on production costs and consumer prices, particularly in carbon‐intensive industries such as electricity generation and transportation. However, as China continues to expand its renewable energy capacity, these price effects are expected to moderate over time. The study also identifies critical economic sectors and mechanisms through which carbon pricing policies influence broader economic dynamics, providing insights into the transmission pathways of these policies. In conclusion, the paper offers policy recommendations tailored to China's implementation of source‐based carbon pricing. These recommendations aim to support the government's ambitious carbon neutrality goals while addressing the economic challenges associated with transitioning to a low‐carbon economy.